Tinjauan Literatur atas Peran Karakteristik Auditor dalam menentukan Fee Audit dan Implikasinya terhadap Kualitas Audit - Rizwandi, Hafiz Fazie; Tantri, Gita Khaliana; Sasmedi, Bagas Fathias; Widaningsih, Mimin (Pusat Riset dan Inovasi Nasional, 2026)
Audit quality is an important aspect in maintaining the credibility of financial statements and reducing information asymmetry between management and stakeholders. Although several studies have examined the relationship between auditor characteristics, audit fees, and audit quality, the findings remain varied and have not been comprehensively reviewed. This article aims to present a literature review on the role of auditor characteristics in determining audit fees and their implications for audit quality. This study employs a literature review method with narrative-qualitative analysis of articles from SINTA and Scopus indexed journals over the past ten years. The results indicate that audit fee determination is influenced by auditor characteristics, including public accounting firm reputation, professional experience, and gender, while also reflecting audit effort intensity, client complexity, and engagement risk. Meanwhile, audit quality is affected by several factors, such as auditor competence and experience, independence, public accounting firm reputation, and auditors’ understanding of clients’ internal control systems. The relationship between audit fees and audit quality shows mixed results, where higher fees may enhance audit quality through increased audit effort, but may also reduce audit quality if they create economic dependence that compromises auditor independence. These findings highlight the importance of considering auditor characteristics in determining audit fees to ensure that audit quality is maintained.